Implementasi Pengorganisasian untuk Meningkatkan Kinerja Amil Pelaksana di BAZNAS Kabupaten Cirebon - Sunengsih, Sunengsih; Sarbini, Ahmad; Rahmawaty, Indira Sabet (Tadbir: Jurnal Manajemen Dakwah, 2022)
The purpose of this study was to determine the mechanism of division of tasks, departmentalization, management hierarchy levels, communication channels, committee functions, management spans and the role of informal groups in improving the performance of the implementing amyl. The method used is descriptive, qualitative method. The results of this study indicate that the division of labor is carried out by grouping amyl into five departments. The level of the hierarchy is very clear. Communication goes well through their respective channels. The committee's function in helping realize the BAZNAS program has been carried out well. The management span is a wide management span. The role of informal groups is to create a positive work atmosphere. So, the implementation of organizing to improve the performance of the implementing amil at BAZNAS Cirebon Regency has been implemented well.